Investigation of performance, combustion and emission characteristics in a diesel engine fueled with methanol/ethanol/nHeptane/diesel blends - VARGÜN, MUSTAFA; SAYIN, CENK; YILMAZ, İLKER TURGUT (My University, 2022)
One of the important reasons of exhaust emissions harmful to the environment and human health is the use of fossil fuels in internal combustion engines as energy resources. In this study, in order to research for cleaner fuel resources and to reduce dependence on fossil fuels, 20% methanol, ethanol and n-heptane fuels added by volume to fossil-based diesel fuel. The effects on engine performance, combustion and exhaust emission characteristics were investigated in a diesel engine with a 4-cylinder common rail injection system, at different engine loads (40 Nm and 80 Nm) and different engine speeds (1500 rpm, 1600 rpm, 1700 rpm and 1800 rpm). The maximum brake thermal efficiency (BTE) value was obtained as 43% with diesel-methanol (M20) mixed fuel at 1800 rpm at 80 Nm engine load. Brake specific fuel consumption (BSFC) values improved in all fuel types with the increase in engine load. In all test conditions, the highest maximum cylinder gas pressure (CPmax) value was obtained with M20 fuel as 114.3 bar, while the highest cumulative heat release (CHRmax) value was determined as 811.7 J with diesel-nheptane (H20) fuel. Compared to diesel fuel (D100), the use of alcohol-diesel fuel mixtures resulted in longer ignition delay (ID) and shortened combustion duration (CD). In general, a significant reduction in carbon dioxide (CO2) emissions has been observed with the use of blended fuels. As a result of the increase in engine the load, a decrease in HC emissions was observed for all test fuels. When compared to D100 fuel, oxygen (O-2) and nitrogen oxide (NO) emissions were increased with the use of diesel-methanol (M20) and diesel-ethanol (E20) fuels, while O-2\ and NO emissions were decreased with the use of diesel-nheptane fuel. (C) 2022 Elsevier Ltd. All rights reserved.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; TERMODİNAMİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENERJİ VE YAKITLAR; THERMODYNAMICS; ENGINEERING; Engineering, Computing & Technology (ENG); ENERGY & FUELS; Genel Mühendislik; Mühendislik (çeşitli); Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Genel Enerji; Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Renewable Energy, Sustainability and the Environment; Fuel Technology; Energy Engineering and Power Technology; Energy (miscellaneous); General Energy; Physical Sciences; Combustion and exhaust emissions; Diesel engine; Ethanol; Methanol; n-Heptane; Performance; N-HEPTANE; EXHAUST EMISSIONS; IGNITION ENGINE; ETHANOL; COMPRESSION; PROGRESS; BUTANOL